From Musaylima to the Khārijite Najdiyya - Al Makin (Al-Jami'ah Research Centre, 2013)
This paper tries to reconstruct the following accounts: the defeat of Musaylima and the death of his prominent followers, and the rise of the Khārijite Najdiyya in Yamama. Moreover, this study seeks the evidence which points to the possible connection between Musaylima’s movement and the Khārijite Najdiyya. This paper highlights that many founders and prominent leaders of the Khārijites, and particularly the Najdiyya sect, came from the tribe of Ḥanīfa, to which Musaylima belonged. This, among other things, seems to have become the main impulse of attraction for the people of Ḥanīfa to join the sect. Additionally, the ‘characteristics’ and the ‘image’ of the Najdiyya reflect those of Musaylima. This leads us to conjecture that the people of Ḥanīfa, having failed to defend their prophet Musaylima and the land of Yamāma against the Medinan caliphate under Abū Bakr in the Battle of ‘Aqraba, later joined the Khārijite Najdiyya.[Artikel ini menjelaskan kekalahan Musaylima dan kematian pengikut-pengikut utamanya serta kemunculan aliran Khawārij Najdiyya di Yamāma. Melalui artikel ini, penulis membuktikan relasi antara gerakan Musaylima dan Khawārij Najdiyya. Ini bisa dibuktikan dengan mencermati fakta bahwa sebagian pendiri dan tokoh utama Khawārij, utamanya sekte Najdiyya, berasal dari suku Ḥanīfa suku yang juga menjadi asal muasal Musaylima. Kesamaan suku inilah dan beberapa faktor lainnya nampaknya menjadi daya tarik tersendiri bagi orang-orang suku Ḥanīfa untuk bergabung dengan sekte Najdiyya. Selain itu, ‘karakteristik’ dan ‘imej’ sekte Najdiyya yang menyerupai gerakan Musaylima adalah hal lain yang turut menguatkan asumsi tersebut. Pandangan inilah yang kemudian mengantarkan penulis pada kesimpulan bahwa setelah gagal mempertahankan nabi mereka, Musaylima, dan wilayah mereka, Yamāma, melawan khilafah Islam di Madinah yang dipimpin Abū Bakr, suku Ḥanīfa memilih memberontak dan bergabung dengan sekte Khawārij Najdiyya.]